Essays on exchange rate volatility and current account adjustments - Tian, Mo (2013)
This thesis empirically assesses exchange rate volatility given the choice of exchange rate regimes and the responses of current account components (trade balance and net investment income flows) to exchange rate fluctuations across countries.